The Effect of Health Belief Model-Based Interventions to Increase Diet Quality of Adolescents - Kisda, Anada Varenza; Ekayanti, Ikeu; Sinaga, Tiurma (Universitas Airlangga, 2024)
The adolescent dietary quality in Indonesia remains subpar, with a substantial proportion of ≤ 95% of adolescents not consuming enough or any fruits and vegetables. The main objective of this research was to evaluate the impact of nutrition education programs based on the Health Belief Model (HBM) and conventional methods on the knowledge, attitudes, and eating habits of adolescents, with the ultimate goal of promoting healthy dietary practices. This study was a quasi-experimental study with a non-randomized control group pre and post-test design to 78 adolescents 13-15 years who met the inclusion criteria at the Bogor Regency Junior High School. Diet quality data was collected using 2x24 hours of food recall. The knowledge, attitude, and health belief model questionnaires that had been collected through questionnaires were then analyzed using SPSS version 25.0 using the Wilcoxon and paired t-test. There was no change in the quality diet in the health belief model and control groups with p-value>0.05. However, there was an increase in knowledge and attitude in both groups with a p-value<0.05. Only three constructs that improved were vulnerability, seriousness and self-efficacy with p-value < 0.05. Perceived benefits, barriers and action cues did not increase with p-value > 0.05. Health belief model nutrition education methods can improve knowledge and attitude, but not give a change in behavior. Health belief model nutrition education method can improve knowledge and attitudes, but not changes in eating behavior. Further health belief model-based nutrition education programs are needed to increase motivation and willingness to act.